Flesh fly (Diptera: Sarcophagidae) survey on coastal environments in northeastern Brazil: new records and notes on the expanded geographical distribution - Barbosa, Taciano Moura; Mello-Patiu, Cátia Antunes; Vasconcelos, Simão Dias (ENTOMOTROPICA, 2015)
Despite the medical, veterinary and forensic relevance of flesh flies (Diptera: Sarcophagidae) species, knowledge on their diversity in Brazil is limited, especially in northeastern Brazil. We performed a survey of Sarcophagidae species in coastal environments in Pernambuco, Brazil, using traps baited with decomposing fish and chicken liver in 2011-2013. Twenty-four species were registered, belonging to ten genera: Argoravinia, Dexosarcophaga, Malacophagomyia, Oxysarcodexia, Peckia, Ravinia, Sarcofahrtiopsis, Titanogrypa, Tricharaea and Villegasia. Peckia villegasi Dodge, 1966 is reported for the first time in Brasil and five Sarcophagidae species in the northeastern region of Brasil. Images of habitus and male terminalia of P. villegasi are also provided for the first time. The results expand the knowledge on the geographical distribution and habitat occupation of the family as well as on their forensic relevance.